Climate change and food security in EAC region: A panel data analysis - Walaa Mahrous (Review of Economics and Political Science (REPS), 2019)
Purpose - This study aims to analyze the impact of global climate change on food security in the East African Community (EAC) region, using panel data analysis for five countries, over 2000-2014. Design/methodology/approach - The determinants of food security are expressed as a function of rainfall, temperature, land area under cereal production, and population size. The paper used pooled fixed effects to estimate the relationship among these variables. Findings - Findings show that food security in EAC is adversely affected by temperature. However, precipitation and increasing areas cultivated with cereal crops will be beneficial to ensure everyone's food security. Originality/value - Actions for mitigating global warming are important for EAC to consolidate the region's economic, political and social development/stability.
Keywords: 330; Climate change; Panel data analysis; Food security; EAC